Digitisation in an Academic Library: A Success Story at Tata Institute of Social Sciences - M. Koganuramath, Muttayya; Angadi, Mallikarjun (DESIDOC Journal of Library & Information Technology, 2010)
Digital libraries were viewed as systems providing a community of users with coherent access to a large, organised repository of information and knowledge. The ability of the user to access, reorganise, and utilise this repository is enriched by the capabilities of digital technology. Digitisation has become important in worldwide efforts to preserve, manage, and provide access to scholarly information. However, digitisation efforts require significant financial investments in infrastructure and technology as well as in human resources for project management. This paper discusses the practical experience of digitisation of two major projects carried out in the library. First one is that of digitisation of 55 volumes (1952-2006) of Sociological Bulletin published by the Indian Sociological Society, New Delhi and digitisation of 67 volumes (1940-2006) of Indian Journal of Social Work published by Tata Institute of Social Sciences, Mumbai. The paper highlights the objectives of the project proposals, justification and anticipated impact, plan for the digitisation, process methodologies for digitisation, volume of work, etc. The paper also describes various steps involved in the digitisation process, OCR software used and its advantages over other OCRs, search interface used, browsing and searching facilities, navigation facilities provided in the CD, etc. Some of the past and present digitisation projects that have been carried out in the library are also mentioned. DOI: 10.14429/djlit.30.283